2020
DOI: 10.1136/jitc-2019-000246
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming hypoxia-induced functional suppression of NK cells

Abstract: BackgroundNatural killer (NK) cells are immune cells capable of killing virally infected cells and tumor cells without the need for antigen stimulation. Tumors, however, can create a suppressive microenvironment that decreases NK function. A feature of many tumors is hypoxia (low oxygen perfusion), which has been previously shown to decrease NK function. A high affinity NK (haNK) cell has been engineered to express a high affinity CD16 receptor as well as internal interleukin (IL)-2 for increased antibody-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 54 publications
1
46
0
Order By: Relevance
“…In addition to infiltration, the solid tumor microenvironment restricts NK cell reactivity. In tumors infiltrated with NK cells that are suppressed, interventions to support NK cell reactivity and overcome immunosuppression, such as checkpoint blockade or local cytokine production may prove efficacious [122] , [123] , [124] , [125] . NK cells isolated from patients with solid tumors including head and neck 126 , 127 , gallbladder 128 , and ovarian 129 cancers exhibit increased expression of inhibitory receptors and decreased expression of activating receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to infiltration, the solid tumor microenvironment restricts NK cell reactivity. In tumors infiltrated with NK cells that are suppressed, interventions to support NK cell reactivity and overcome immunosuppression, such as checkpoint blockade or local cytokine production may prove efficacious [122] , [123] , [124] , [125] . NK cells isolated from patients with solid tumors including head and neck 126 , 127 , gallbladder 128 , and ovarian 129 cancers exhibit increased expression of inhibitory receptors and decreased expression of activating receptors.…”
Section: Discussionmentioning
confidence: 99%
“…HIF‐1α regulates gene expression programs involved in many processes, such as cell proliferation, survival, glucose metabolism, and angiogenesis 49 . It has been demonstrated that NK cells are hyporesponsive under hypoxic conditions in vitro , displaying reduced expression of NKG2D, CD107a, and granzyme B with concomitant reductions in cytotoxicity 49–52 . Similarly, human peripheral NK cells cultured under hypoxic conditions in vitro displayed reduced IFN‐γ, granzyme B, and CD107a protein levels that could be restored using a HIF‐1α inhibitor 53 .…”
Section: Immunosuppressive Factors In the Tumor Microenvironmentmentioning
confidence: 99%
“…49 It has been demonstrated that NK cells are hyporesponsive under hypoxic conditions in vitro, displaying reduced expression of NKG2D, CD107a, and granzyme B with concomitant reductions in cytotoxicity. [49][50][51][52] Similarly, human peripheral NK cells cultured under hypoxic conditions in vitro displayed reduced IFN-c, granzyme B, and CD107a protein levels that could be restored using a HIF-1a inhibitor. 53 Experiments using in vivo tumor models have proposed that HIF-1a À/À NK cells promote tumor clearance by inhibiting vascular endothelial growth factor (VEGF)-driven angiogenesis.…”
Section: Immunosuppressive Factors In the Tumor Microenvironment Hypoxiamentioning
confidence: 99%
“…Hypoxic stress within the tumor microenvironment shapes the NK cell phenotype, thereby inducing tumor resistance and generating immune-suppressive cells. For example, exposure of NK cells to hypoxic conditions of 1% pO 2 resulted in drastic suppression of NK cytotoxicity against natural tumor targets [ 10 , 11 , 12 ]. Furthermore, tumor cells themselves adopt several strategies to evade NK cell-mediated killing by directly downregulating NK-activating receptors and/or indirectly releasing immunosuppressive factors such as TGFβ, IL-10, IDO, and soluble NK receptor ligands, namely ULBPs and MICA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%